Финикийская концепция создания мира из влаги - Рассоха, И.Н. (Культура народов Причерноморья, 2013)
Ключевая идея финикийской философии - о том, что Вселенная возникла из соединения неоформленной материи, представляемой как вода («Предначальные воды») и/или ил, с Богом-Творцом, представляемым как Ум, Слово (Логос), Дух и в то же время Свет. Эта идея изложена в космогонии Санхунйатона и, вероятно, восходит к древнеегипетской традиции веры Единого Бога-Творца, Атона. От финикийцев эту идею позаимствовали как евреи в Библии и Каббале, так и древнегреческие философы, прежде всего Фалес и стоики. Ключова ідея фінікійської філософії - про те, що Всесвіт виник із з'єднання неоформленої матерії, що уявляється як вода («Предковічні води») та / або мул, з Богом-Творцем, репрезентованим як Розум, Слово (Логос), Дух і водночас Світло. Ця ідея викладена в космогонії Санхунйатона і, ймовірно, сходить до давньоєгипетської традиції віри в Єдиного Бога-Творця, Атона. Від фінікійців цю ідею запозичили як євреї в Біблії і Каббалі, так і давньогрецькі філософи, насамперед Фалес і стоїки. The key idea of the Phoenician philosophy - that the Universe originated from a compound of unformed matter, provided the water ("Pre-Origin Water") and / or Silt, with God the Creator, represented as Mind, the Word (Logos), the Spirit, and especially the Light. This idea is presented in the Sanhunyaton's cosmogony and probably dates back to the ancient traditions of the faith of the One God, the Creator, Aten. From the Phoenicians borrowed this idea as the Jews in the Bible and the Kabbalah, and the ancient Greek philosophers, especially Thales and the Stoics.